Hubungan Stres Dan Emotional Eating Dengan Status Gizi Pada Mahasiswa Kedokteran Fk Untar - Bunga Sherley Aprilia; Olivia Charissa (Fakultas Ilmu Kesehatan Universitas Gresik, 2023)
Stress is a condition caused when a person or environment related to the individual, namely between the desired situation and biological, psychological or social system. Stress can affect eatung behavior so that it ultimately affects the nutritional status of students. The purpose of this study is to determine the relationship between stress and emotional eating with nutritional status in medical students. This research is an analytic study with a cross-sectional design. Respondents were obtained through the Adult Eating Behaviour Questionnaire (AEBQ) and the DASS (Depression Anxiety Stres Scales) questionnaire. Anthropometric data obtained through measurements. Data analysis using chi-square statistical test. Results From 192 respondents, the incidence of stress was found to be 70,3%. For emotional eating, most of them get emotional over eating. Most of the respondents nutritional status experienced abnormal nutritional status (57,3%). The results showed that there was no relationship between stress and nutritional status (p-value = 0,956) and there was a relationship between emotional eating and nutritional status (p-value = 0,017). Conclusion : There is no relationship between stress and nutritional status, but the stressed group has a lower risk of experiencing abnormal nutritional status than those who are not stressed (p-value = 0,956). Meanwhile, there is a relationship between emotional eating and over nutritional status, many experience abnormal nutritional status in those are emotional under eating or emotional over eating (p-value = 0,017).